Reframing 'Gastarbeiter' Migration: Family, Photography and Cultural Memory in Almanya — Willkommen in Deutschland. - Leworthy, Paul (Oxford German Studies, 2023)
Interpreting it as constitutive and representative of the film's exploration of cultural memory processes, this article identifies an abundance of frames in Almanya — Willkommen in Deutschland. Visual frames — frequently in the form of photographs — abound in the film. At the same time, the film's narrative structure entwines present and past temporal frames, with the latter embedded into the former through acts of intradiegetic narration. As well as accentuating the essential role played by narrative in present constructions of the past and pointing to the family as a key 'social frame of memory', both the visual and structural frames in the film accentuate the limited perspective of any retrospective account, which invariably frames the past in a specific — and selective — way. I also expose that Almanya — Willkommen in Deutschland is memory-productive as well as memory-reflective: the film does not only illustrate cultural memory processes in action within the narrative, it also contributes a new narrative about 'Gastarbeiter' migration from Turkey to Germany. Considering the film's popularity with audiences in Germany as evidence of the broad reach of its memory narrative, I conclude that the film constitutes a self-conscious and situated, constructive and successful contribution to twenty-first-century German cultural memory.